Smoking and stroke: A mendelian randomization study - Larsson, Susanna C. (Ann Neurol, 2019)
We used the Mendelian randomization design to explore the potential causal association of smoking with ischemic stroke and intracerebral hemorrhage using summary statistics data for 34,217 ischemic stroke cases and 404,630 noncases, and 1,545 cases of intracerebral hemorrhage and 1,481 noncases. Genetic predisposition to smoking initiation (ever smoking regularly), based on up to 372 single‐nucleotide polymorphisms, was statistically significantly positively associated with any ischemic stroke, large artery stroke, and small vessel stroke but not cardioembolic stroke or intracerebral hemorrhage. This study provides genetic support for a causal association of smoking with ischemic stroke, particularly large artery and small vessel stroke. ANN NEUROL 2019;86:468–471